2016
DOI: 10.1038/ng.3627
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic architectures for syndromic and nonsyndromic congenital heart defects identified by exome sequencing

Abstract: Congenital Heart Defects (CHD) have a neonatal incidence of 0.8-1%1,2. Despite abundant examples of monogenic CHD in humans and mice, CHD has a low absolute sibling recurrence risk (~2.7%)3, suggesting a considerable role for de novo mutations (DNM), and/or incomplete penetrance4,5. De novo protein-truncating variants (PTVs) have been shown to be enriched among the 10% of ‘syndromic’ patients with extra-cardiac manifestations6,7. We exome sequenced 1,891 probands, including both syndromic (S-CHD, n=610) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
439
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(460 citation statements)
references
References 41 publications
14
439
2
5
Order By: Relevance
“…The etiology for these cases is proposed to be multifactorial, as demonstrated in epidemiological studies, which show a significant role for both genetic and environmental determinants (4)(5)(6). Studies of genetic contributors have identified an increasing number of genes associated with CHD (7)(8)(9). The importance of gene dosage for the occurrence of cardiac malformations has been shown, along with the concept of an oligogenic etiology for CHD, supporting the concept that mild alterations in gene expression levels may lead disease phenotypes (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 86%
“…The etiology for these cases is proposed to be multifactorial, as demonstrated in epidemiological studies, which show a significant role for both genetic and environmental determinants (4)(5)(6). Studies of genetic contributors have identified an increasing number of genes associated with CHD (7)(8)(9). The importance of gene dosage for the occurrence of cardiac malformations has been shown, along with the concept of an oligogenic etiology for CHD, supporting the concept that mild alterations in gene expression levels may lead disease phenotypes (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 86%
“…For these milder phenotypes that have less impact on fitness, the exact contribution of de novo mutations to the disease burden is not yet firmly established, and inherited variation is likely to be at least as important in the expression of the phenotype [120122]. Next to neurodevelopmental disorders, de novo mutations also play a prominent role in pediatric diseases such as congenital heart defects (CHDs) [123125]. In agreement with the observation made in neurodevelopmental disorders, recent studies found the highest contribution of de novo mutations to disease in individuals with the most severe and syndromic forms of CHD [123, 125].…”
Section: De Novo Mutations In Human Diseasementioning
confidence: 99%
“…Eine große Problematik ergibt sich jedoch aus der Tatsache, dass viele der Gene nur eine unzureichende Assoziation mit den zugrunde liegenden Herzfehlern zeigen und zum aktuellen Zeitpunkt nicht als kausal betrachtet werden können. Im Gegensatz zu den syndromalen Herzfehlern lassen sich bei isolierten Herzfehlern zu einem weitaus geringeren Prozentsatz De-novo-Mutationen nachweisen [6,14]. Außerdem zeigt sich eine Anhäufung von seltenen proteintrunkierenden Varianten, welche von einem gesunden Elternteil vererbt worden sind.…”
Section: Nicht-syndromale Strukturelle Herzfehlerunclassified